Spatholirion cucphuongense (Commelinaceae), a new species from Cuc Phuong National Park in North Vietnam - Lin, Che-Wei; Peng, Ching-I; Nguyen, Hieu Quang; Nguyen, Tien Hiep; Kono, Yoshiko (Phytotaxa, 2023)
A new species, Spatholirion cucphuongense (Commelinaceae) is described and illustrated from northern Vietnam. Morphologically it resembles to S. ornatum, but differs in its lamina with greyish-white markings on adaxial surface (vs. absent markings, sometimes ornamented when young with white markings), lower surface lateral veins glabrous (vs. densely velutinous), inflorescence raceme (vs. panicle) of staminate flowers, and sepals dark indigo (vs. pale purple). Moreover, the diploid chromosome number 2n = 60 is observed in the new species, which is unusual in the genus Spatholirion (2n = 20). The new chromosome count also confirms the occurrence of natural polyploids in Spatholirion. The comparative account of chromosome count in the subtribe Streptoliriinae is also provided.